Atypical Peripheral Ossifying Fibroma of the Mandible - Tomislav Katanec; Lea Budak; Davor Brajdić; Dragana Gabrić (MDPI AG, 2022)
Peripheral ossifying fibroma (POF) is a benign localized lesion originating from gingival and alveolar oral mucosa. Its origin can be cells of periodontal ligament. The lesions usually develop in women in their twenties. POF is a complex clinical and histological diagnosis due to its shared characteristics with many other conditions. In this paper, we presented a case of an atypical peripheral ossifying fibroma (POF) in the left lateral part of the mandible in a 70-year-old male patient who had two semicircular bridges supported on four implants in the upper and lower jaws. A review of CBCT and orthopedic imaging showed no visible intraosseous changes. Histological analysis revealed the diagnosis of POF. The case in question is interesting, as elaborated on in the discussion section of this paper because POF is usually found in female patients aged between 20 and 30 years.